1997
DOI: 10.1063/1.366123
|View full text |Cite
|
Sign up to set email alerts
|

Phase and microstructure investigations of boron nitride thin films by spectroscopic ellipsometry in the visible and infrared spectral range

Abstract: Frank, "Phase and microstructure investigations of boron nitride thin films by spectroscopic ellipsometry in the visible and infrared spectral range" (1997 Spectroscopic ellipsometry over the spectral range from 700 to 3000 cm Ϫ1 and from 1.5 to 3.5 eV is used to simultaneously determine phase and microstructure of polycrystalline hexagonal and cubic boron nitride thin films deposited by magnetron sputtering on ͑100͒ silicon. The results are obtained from a single microstructure-dependent model for both infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…8 Infrared ͑IR͒ 4,[9][10][11][12][13][14] and Raman spectroscopy, [15][16][17][18][19][20] as well as IR and visible-light ͑VIS͒ spectroscopic ellipsometry ͑SE͒ [21][22][23][24][25] were used to investigate BN thin-film optical and structural properties. It was demonstrated that polarized IR reflection ͑PIRR͒ measurements, 26,27 IR-SE [28][29][30][31][32][33][34] and VIS-SE 25,30 are useful techniques to resolve the BN microstructure from the thin-film optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…8 Infrared ͑IR͒ 4,[9][10][11][12][13][14] and Raman spectroscopy, [15][16][17][18][19][20] as well as IR and visible-light ͑VIS͒ spectroscopic ellipsometry ͑SE͒ [21][22][23][24][25] were used to investigate BN thin-film optical and structural properties. It was demonstrated that polarized IR reflection ͑PIRR͒ measurements, 26,27 IR-SE [28][29][30][31][32][33][34] and VIS-SE 25,30 are useful techniques to resolve the BN microstructure from the thin-film optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to application of sputter-deposited films it is necessary to understand the relation between microstructure, growth conditions, and resulting electrical and optical properties. A through optical study of such microstructure related effects was shown previously for magnetron sputtered boron nitride thin films [18][19][20][21] Tantalum oxide films ͑TOF͒ have been grown by a large variety of physical vapor deposition and chemical vapor deposition ͑CVD͒ processes, including ion beam sputtering, 22,23 magnetron sputtering, 2,7,9,24 ͑low temperature͒ thermal oxidation, 9,25 anodization, 26 ion plating, 1,27 electronbeam evaporation, 4,27 laser ablation, 28,29 low pressure CVD, 14,30 photo-CVD, 31,32 atomic layer deposition, 33 and plasma-enhanced CVD. 12,16,34 A metalorganic solution deposition technique 6 was also used to grow TOF.…”
Section: Introductionmentioning
confidence: 99%
“…20 The h-BN optical response was recently investigated by ex situ multiple angle-of-incidence spectroscopic ellipsometry, and found to be anisotropic. 19,20 This anisotropy, however, is difficult to observe at the single angle of incidence used for in situ ellipsometry. The optical responses of both h-BN (n h ), and c-BN (n c ) are treated as isotropic in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Ex situ ellipsometry was recently used to determine the isotropic c-BN ͑e.g., at ϭ571 nm: n c ϭ2.1͒, and anisotropic h-BN ͑n e ϭ1.65, n o ϭ2.1͒ optical constants and thin-film layer structure of magnetron sputtered BN. [19][20][21] . It was observed that the h-BN and c-BN thin-film optical constants are very similar to their bulk values.…”
Section: ͑1͒mentioning
confidence: 99%